Hydrogen Limits Carbon in Liquid Iron. Issue 10 (22nd May 2019) - Hirose, Kei; Tagawa, Shoh; Kuwayama, Yasuhiro; Sinmyo, Ryosuke; Morard, Guillaume; Ohishi, Yasuo; Genda, Hidenori
Abstract: Melting experiments were performed on the Fe‐C‐H system to 127 GPa in a laser‐heated diamond anvil cell. On the basis of in situ and ex situ sample characterizations, we found that the solubility of carbon in liquid Fe correlates inversely with hydrogen concentration at ~60 GPa and ~3500 K, indicating that liquid Fe preferentially incorporates hydrogen rather than carbon under conditions with abundant C and H. While large amounts of both C and H may have been delivered to the growing Earth, C‐poor/H‐rich metals were likely added to the protocore in the late stages of core formation. We also obtained a melting curve of FeH x ( x > 1) far beyond the pressure range in earlier determinations. Its liquidus temperature was found to be 2380 K at 135 GPa, lower than those of Fe alloyed with the other possible core light elements. Relatively low core temperature is thus supported by the presence of hydrogen. Plain Language Summary: Both carbon and hydrogen are possible major light elements in the core but estimation of their abundance in the core as well as in the bulk Earth is difficult because of their high volatility. In addition, the property of hydrogen‐bearing iron alloys has been the least studied. Here we performed melting experiments on Fe‐C‐H to 127 GPa, close to the pressure at the top of the Earth's core. Our main finding is that hydrogen limits the solubility of carbon in liquid Fe; the carbon content correlates inversely with hydrogen concentration in molten Fe coexisting with diamonds at ~60 GPa and ~3500 K. Recent planet formation theories suggest that large amounts of C and H were delivered to the growing Earth. In the late stages of core formation, liquid metals preferentially incorporating hydrogen rather than carbon may have added to the protocore. We also found that hydrogen decreases the melting temperature of Fe remarkably. The melting temperature of FeH x ( x > 1) is only about 2380 K at the core‐mantle boundary; lower than those of Fe‐Fe3 S eutectic and Fe alloyed with the other possible core light elements. Key Points: Melting experiments on the Fe‐C‐H system were performed to 127 GPa Hydrogen limits the solubility of carbon in liquid iron Melting temperature of FeH x ( x > 1) is about 2380 K at 135 GPa, lower than those of Fe alloyed with the other possible core light elements